Teacher Job Satisfaction: The Importance of School Working Conditions - Tuteja, Dr. Amit (The journal of contemporary issues in business and government, 2019)
The goal of the study was to look into and examine the influence of work satisfaction and dissatisfaction on women instructors’ commitment to teaching. An initial sample of 1000 female elementary school teachers who had worked in their department for more than five years was taken from four districts in Kashmir valley. The final sample was obtained after the original sample was subjected to the Quartile Deviation (Q3) and Q1 techniques. The researchers employed Meena Buddhisagar Rathod and Madhulika Verma’s "Teacher’s Role Commitment Scale (TRCS)" and Meera Dixit’s "Job Satisfaction Scale for Teacher (JSST)" respectively. The data was statistically treated appropriately, with Mean, Standard Deviation (SD), and a test of significance ("t"- test) being used. Job Satisfied and Dissatisfied women instructors differ considerably on all variables, including the composite score of Role Commitment, according to the data. This evidence indicated the superiority of Job Satisfied instructors in terms of role commitment over Job Dissatisfied teachers.